Smoking habit and cardiac risk index in areas with different levels of urban compactness - Demara Yedhi Azlia; M. Lutfan Lazuardi; Arta Farmawati; Muhammad Sani Roychansyah (Universitas Gadjah Mada, 2021)
Purpose: To determine the relationship between urban compactness level, smoking habit, and CRI in Yogyakarta Urban Agglomeration (YUA) region population. Method: This cross-sectional study used secondary data of 181 male subjects aged 24-52 years who lived in the YUA region to analyze the relationship using the chi-square test. Results: The relationship between urban compactness level with smoking habits showed a value of p=0.075, and the relationship between urban compactness level with CRI showed a value of p=0.181. On the other hand, the relationship between smoking habits with CRI showed a value of p=0.008. Conclusion: Smoking habit had a significant association with CRI in the YUA area population, but not in the level of urban compactness with smoking habit nor CRI.